The Optimum design of Flat Rectrangular Concrete Plates supporting loads in Buidling structures and tests on a one-third full size experimental model - Groyer, Edward (Department of Civil Engineering, 2015)
The popularity of concrete flat plate construction in Building Structures has soared in the last 20 years but their design has been based mainly on their ultimate strength rather than their behaviour in terms of deflection and cracking at working loads. As a result their deflections have been larger than anticipated and have caused displacements and severe cracks in masonry partitions which are being supported. In order to design any rectangular flat plate for optimum performance and economy most of the present design procedures such as the Elastic, Empirical, Yield-Line, Elastic-Plastic and Finite Difference, are reviewed, critically examined and illustrated by designing the same typical flat plate consisting of three bays in each direction for a uniformly distributed transverse load. Comparisons are made of the cost, strength and behaviour of each resulting plate.